The prevalence of barriers for Colombian college students engaging in physical activity (2015)
Objective: To investigate the prevalence of barriers and their association with Colombia college students engaging in PA. Methods: A total of 5,663 students (3,348 male) from three cities in Colombia. In fall 2013, students voluntarily completed a demographic questionnaire, Barriers to Being Active Quiz. Logistic regression analysis of each barrier (adjusted for confusion variables: gender, age and BMI) was used for verifying such association. Results: The most prevalent barriers in overweight individuals were “fear of injury” (87.0%), “lack of skill” (79.8%) and “lack of resources” (64.3%). The group of females revealed a protective association regarding “lack of time” (OR=0.53: 0.47-0.60 95%CI), “social influence” (OR=0.67: 0.60-0.75 95%CI), “lack of energy” (OR=0.54: 0.49-0.61 95%CI), “lack of willpower” (OR=0.57: 0.51- 0.64 95%CI), “lack of skill” (OR=0.76: 0.66-0.87 95%CI) and “lack of resources” (OR=0.79: 0.71-0.89 95%CI). Such observation also appeared in the 20- to 23-yearold age group concerning “social influence” (OR=0.83: 0.74-0.94 95%CI) and in those aged over 23-years-old (OR=0.86: 0.74-0.99 95%CI) regarding “lack of energy”. Conclusion: A significant prevalence was found regarding self-perception of barriers leading to students ceasing to engage in PA. © 2015, Grupo Aula Medica S.A. All rights reserved.